Anemia in Indian Men Predicts Fewer Work Hours and Lower Earnings: Evidence from Nationally Representative Health and Labor Surveys. (29th May 2020) - Scott, Samuel; Pant, Anjali; Nguyen, Phuong; Alderman, Harold; Yadav, Kapil; Menon, Purnima
Abstract: Objectives: Anemia is globally recognized as an important public health problem in women and children, thus the consequences of anemia have predominantly been described in these two groups. India's large population, high anemia prevalence and male-dominated workforce imply that productivity consequences of anemia in men could have large implications. We sought to explore the association between local anemia rates and productivity outcomes in Indian men. Methods: Data on anemia were from the 2015–2016 National Family Household Survey (NFHS) and data on productivity outcomes—number of hours works and total earnings in the last week—were from the 2017–2018 Periodic Labour Force Survey (PLFS), for a combined sample of 245, 073 men aged 15–54 years. NFHS was collapsed at three levels (district, urban/rural, and five-year age brackets; n = 9818) and then merged with the full PLFS sample to generate an analytical sample of 135, 500 observations. We report sample means using survey weights. Individual-level productivity outcomes were regressed on means from the collapsed data using ordinary least squares regression, adjusting for state of residence, age and education. The primary predictor was anemia quintile, with anemia defined as hemoglobin below 130 g/L from a finger-prick blood sample. Results: Anemia affected 23% of men aged 15–54 years in India in 2016 and was more common in rural (25%) than urban (19%) areas. On average, men worked 51.5 hours and earned 2430 Indian Rupees in the last week. In the adjusted models, being in the top quintile of anemia prevalence (ref: lowest quintile) predicted 2.1 fewer hours worked (95% CI 1.5–2.8) and 240 less rupees earned (95% CI 173–307) in the last week ( P  < 0.001 for both). These effects translate to 4% lost work hours and 10% lost earnings related to anemia. Conclusions: Nearly one in four men are anemic in India and our findings suggest that anemia is associated with reduced productivity at the population level. Anemia reduction policies and programs in India should work toward the inclusion of men. Funding Sources: Agriculture for Nutrition and Health/IFPRI.